A Flexible Solution for TD-LTE Indoor Coverage Enhancement：Relay - Jianjun Liu; Xiaodong Shen; Zhenping Hu; Yu Qian; Zhiheng Guo (Dianxin kexue)
TD-LTE will be deployed on high frequency band，facing with the issue of larger propagation loss and penetration loss，which brings a big challenge to future indoor deep coverage. Based on clarifying the requirement of TD-LTE outdoor to indoor deployment，and also combined with the field trial in the real network，the performance of indoor coverage enhancement using relay was analyzed. Test results show that deploying relay outside buildings and enhancing the deep coverage from outdoor to indoor is a fast，flexible and low cost solution for the buildings without the wired backhau1.